Landasan Syariah Dalam Pengelolaan Pengembangan Pendidikan Karakter Islam - Jufri Jufri (TADRIBUNA: Journal of Islamic Education Management, 2026)
Islamic character education is an important part of shaping the personality of students who have noble character, faith, and responsibility in social life. This research aims to analyze the foundation of sharia in the development of Islamic character education based on the Qur'an, hadith, and contemporary Islamic educational thought. This research uses a type of library research with a qualitative-descriptive approach. Data sources were obtained from scientific literature, national and international journals, books of tafsir, hadith, and relevant academic documents in the last seven years. Data collection techniques are carried out through documentation and literature studies, while data analysis uses content analysis techniques. The results of the study show that the sharia foundation of Islamic character education is rooted in the values of monotheism, morals, worship, and muamalah which are integrated in human life. Character education in Islam is not only oriented towards the formation of individual morality, but also the building of social piety. The novelty of this research lies in the integration between sharia principles and strengthening the character of students in the context of modern education based on spiritual and social values. This research contributes to the development of Islamic character education models that are relevant to the challenges of globalization and moral crises in the digital era.